Low temperature crystal structure of natural diosgenone - Piro, Oscar Enrique (2002)
The molecular structure of diosgenone, a natural steroidal sapogenin, closely related to diosgenin and isolated from Solanum nudum, was solved by single crystal X-ray diffractometry at 120 K and refined by full-matrix least-squares to an agreement factor, R1 = 0.054. It crystallizes in the monoclinic space group P21, with a = 15.1870(4) Å, b = 7.2710(2) Å, c = 21.2840(6) Å, β = 99.251(1)°, and four molecules in the unit cell (Z = 4). The results constitute the first structural report on a steroidal sapogenin from the diosgenin group.